Influenza surveillance in the Pacific Island countries and territories during the 2009 pandemic: an observational study - Kool, Jacobus Leen (BioMed Central, 2013)
BACKGROUND: Historically, Pacific island countries and territories (PICTs) have been more severely affected by influenza pandemics than any other part of the world. We herein describe the emergence and epidemiologic characteristics of pandemic influenza H1N1 in PICTs from 2009 to 2010. METHODS: The World Health Organization gathered reports of influenza-like-illness and laboratory-confirmed pandemic H1N1 cases from all 23 Pacific island countries and territories, from April 2009 through August 2010. Data were gathered through weekly email reports from Pacific island countries and territories and through email or telephone follow-up. RESULTS: Pacific island countries and territories started detecting pandemic H1N1 cases in June 2009, firstly in French Polynesia, with the last new detection occurring in August 2009 in Tuvalu. Nineteen Pacific island countries and territories reported 1,972 confirmed cases, peaking in August 2009. No confirmed pandemic H1N1 cases were identified in Niue, Pitcairn and Tokelau; the latter instituted strict maritime quarantine. Influenza-like-illness surveillance showed trends similar to surveillance of confirmed cases. Seven Pacific island countries and territories reported 21 deaths of confirmed pandemic H1N1. Case-patients died of acute respiratory distress syndrome or multi-organ failure, or both. The most reported pre-existing conditions were obesity, lung disease, heart disease, and pregnancy. Pacific island countries and territories instituted a variety of mitigation measures, including arrival health screening. Multiple partners facilitated influenza preparedness planning and outbreak response. CONCLUSIONS: Pandemic influenza spread rapidly throughout the Pacific despite enormous distances and relative isolation. Tokelau and Pitcairn may be the only jurisdictions to have remained pandemic-free. Despite being well-prepared, Pacific island countries and territories experienced significant morbidity and mortality, consistent with other indigenous and low-resource settings. For the first time, regional influenza-like-illness surveillance was conducted in the Pacific, allowing health authorities to monitor the pandemic’s spread and severity in real-time. Future regional outbreak responses will likely benefit from the lessons learned during this outbreak.